Implementation of A Total Ergonomics Approach To Improve the Quality of Life of Freight Workers In 16 Ilir Market, Palembang City, South Sumatera Province - Setiawan, Heri; Susanto, Sani; Rinamurti, Micheline; Pratama, Yohanes Dicka (Ann Publisher, 2024)
The results of preliminary observations of the working conditions and environment of freight workers in the 16 Ilir Market, Palembang City, South Sumaetera Province are categorized as less ergonomic in physical, work environment, psychological, organizational and management aspects. Freight workers work by placing baskets on their heads, on their backs and even some without tools directly on their shoulders which load basic food items, and loading-unloading warehousing goods, weighing ±35 kg, a distance of ±500 meters with a low level of productivity. After finishing work, freight workers experience aches all throughout the body, particularly in the legs and neck, as well as waist and back pain. Based on work pulse frequency, the workload was determined to be 131.25±14.10 beats per minute, and it was categorized as heavy work. The fatigue score reached 69.10±15.29 and the musculoskeletal disorder score was 61.25±7.44. The method used is a total ergonomics approach, to enhance work productivity by reducing workload, fatigue, and musculoskeletal system issues. Thirty research samples were chosen by simple randomization of freight workers for this same-subject experimental study. The Wilcoxon Signed Rank Test and the t-paired test were used to evaluate the data at a 5% significance level. Workload, weariness, and musculoskeletal complaints significantly decreased, and productivity increased (p<0.05), according to the data. In conclusion, the total ergonomics approach reduced workload as seen from the decrease in: work pulse rate by 15.61%, fatigue by 58.97%, musculoskeletal system complaints by 28.78%. Consequently, there was a 21.00% increase in productivity. The total ergonomics approach can improve the quality of life and work productivity of freight workers in 16 Ilir Market, Palembang City, South Sumatera Province